Sialidase NEU3 contributes neoplastic potential on colon cancer cells as a key modulator of gangliosides by regulating Wnt signaling. Issue 7 (1st April 2015) - Takahashi, Kohta; Hosono, Masahiro; Sato, Ikuro; Hata, Keiko; Wada, Tadashi; Yamaguchi, Kazunori; Nitta, Kazuo; Shima, Hiroshi; Miyagi, Taeko
<x xml:space="preserve">Abstract</x> The plasma membrane‐associated sialidase NEU3 is a key enzyme for ganglioside degradation. We previously demonstrated remarkable up‐regulation of NEU3 in various human cancers, with augmented malignant properties. Here, we provide evidence of a close link between NEU3 expression and Wnt/β‐catenin signaling in colon cancer cells by analyzing tumorigenic potential and cancer stem‐like characteristics. NEU3 silencing in HT‐29 and HCT116 colon cancer cells resulted in significant decrease in clonogenicity on soft agar and in vivo tumor growth, along with down‐regulation of stemness and Wnt‐related genes. Analyses further revealed that NEU3 enhanced phosphorylation of the Wnt receptor LRP6 and consequently β‐catenin activation by accelerating complex formation with LRP6 and recruitment of GSK3β and Axin, whereas its silencing exerted the opposite effects. NEU3 activity‐null mutants failed to demonstrate the activation, indicating the requirement of ganglioside modulation by the sialidase for the effects. Under sphere‐forming conditions, when stemness genes are up‐regulated, endogenous NEU3 expression was found to be significantly increased, whereas NEU3 silencing suppressed sphere‐formation and in vivo tumor incidence in NOD‐SCID mice. Increased ability of clonogenicity on soft agar and sphere formation by Wnt stimulation was abrogated by NEU3 silencing. Furthermore, NEU3 was found to regulate phosphorylation of ERK and Akt via EGF receptor and Ras cascades, thought to be additionally required for tumor progression. The results indicate an essential contribution of NEU3 to tumorigenic potential through maintenance of stem‐like characteristics of colon cancer cells by regulating Wnt signaling at the receptor level, in addition to tumor progression via Ras/MAPK signaling.